Application of ORYZA1 model to double rice-cropping region in Central China - Pan, Jun; Upasena, Selawa H.; Boonjit Titapiwatanakun; Demaine, Harvey; Government of Japan (Bangkok : Asian Institute of Technology, 1994)
The Central China double rice cropping region was the most important rice-cropping region in China. Fengshui village of Tonglu county in Zhejiang province and Dongshan village of Jurong county in Jiangsu province respectively were selected as study sites. The rice crop growth data and weather data were collected from secondary sources. The socio economic data were collected from 60 farm households. The model ORYZAl was used as a tool in this study with system analysis, economic analysis and farming system research (FSR) approach. The results indicate that the double rice with triple cropping system is the dominant cropping system in study sites, and several constraints do exist in the site. The grain yield of 8.0 t/ha and 7.3 t/ha, and 8.7 t/ha and 8.2 t/ha respectively are predicted by the simulated model ORYZAl, with popular varieties of first rice crop and second rice crop in the two study sites. Compared to observed values of grain yield, a yield gap is only 1.3 t/ha. Economic analysis indicates that the rice cropping system is relatively stable and insensitive to external changes in the environment. The income and expenditure of farm family is greatly affected by labour employed off-farm. Finally, several measures and pathways were put forward to recommend optimum cultural management practices for farmers to increase the rice productivity more efficiently.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources & Development
Thesis (M.Sc.) - Asian Institute of Technology, 1994
Keywords: Double cropping -- China, Central; Rice -- China, Central -- Planting